Calcinosis Cutis Associated with Chronic Sclerodermoid Graft versus Host Disease: A Case and Review of the Literature. (28th February 2020) - Deen, Jacqueline; Byrom, Lisa; Robertson, Ivan
Abstract : We present a rare case of calcinosis cutis associated with chronic sclerodermoid graft versus host disease in a 59-year-old male, 13 years following allogenic bone marrow transplantation. The etiology of calcification was thought to be dystrophic. Further research is needed to understand the link between calcinosis cutis and chronic sclerodermoid graft versus host disease to assist with selecting appropriate management for these patients.